Extração e exportação de nutrientes em cultivares de feijoeiro, sob níveis de adubação: I - Macronutrientes - Soratto, Rogério Peres [UNESP]; Fernandes, Adalton Mazetti [UNESP]; dos Santos, Letícia Andriani [UNESP]; Job, André Luiz Gomes [UNESP] (FapUNIFESP (SciELO), 2013)
The use of cultivars with a higher yield potential and the adoption of new technology have achieved high grain yields in common bean, which probably changed the demand for nutrients in this crop. However, there is almost no information about the periods of the cycle in which nutrients are most demanded at which quantities by the main cultivars. The objective of this study was to evaluate the macronutrient extraction and exportation by the common bean cultivars Pérola and IAC Alvorada, under different levels of NPK fertilization, on a dystroferric Red Nitosol, in Botucatu, São Paulo State, Brazil. The experiment was arranged in a randomized complete block (split plot) design with four replications. The plots consisted of six treatments based on a 2 x 3 factorial model, represented by two cultivars and three NPK levels (PD0 - 'Pérola' without fertilization, PD1 - 'Pérola' with 50 % of recommended fertilization, PD2 - 'Pérola' with 100 % of recommended fertilization, AD0 - 'IAC Alvorada' without fertilization, AD1 - 'IAC Alvorada' with 50 % of recommended fertilization, and AD2 - 'IAC Alvorada' with 100 % of recommended fertilization) and subplots sampled seven times during the cycle. At higher levels of NPK fertilization, the grain yield and macronutrient extraction and exportation of both cultivars were higher, but without statistical differences. Macronutrient absorption was higher in the treatments with 100 % of recommended NPK fertilization (average amounts per hectare: 140 kg N, 16.5 kg P, 120 kg K, 69 kg Ca, 17.9 kg Mg, and 16.3 kg S). Regardless of the treatment, the demand for N, P, K, Ca, and Mg was highest from 45 to 55 days after emergence (DAE), i.e., in the R7 stage (pod formation), while the highest S absorption rates were concentrated between 55 and 65 DAE. More than 70 % of P, between 58 and 69 % of N, 40 and 52 % of S, 40 and 48 % of K, and 35 and 45 % of Mg absorbed during the cycle was exported with grains, whereas less than 15 % of Ca was exported.
Nutrient extraction and exportation by common bean cultivars under different fertilization levels: I - Macronutrients
Keywords: Absorption curves; Absorption rates; Mineral nutrition; Nutrients accumulation; Phaseolus vulgaris